Impact of Money Supply and Interest Rate on Stock Market Performance: Evidence from the Nepalese Capital Market - Subedi, Khem Raj (INTELLIGENCE Journal of Multidisciplinary Research, 2025)
This study examines the influence of money supply and interest rate including other macroeconomic variables on stock market performance in Nepal, using the data spanning from 1994 to 2023. The study employs the ARDL model of co-integration analysis to examine the long-run and short-run relationships between the NEPSE index and some selected macroeconomic variables, including broad money supply, interest rates, real GDP, and remittance inflow. The findings reveal unidirectional causality from broad money supply to NEPSE index, by-directional causality between real GDP and NEPSE index, and unidirectional causality between remittance flow and NEPSE index, but absence of causality between interest rate and NEPSE index. Moreover, the findings reveal that the money supply significantly and positively affects the NEPSE index, both in the long run and the short run, highlighting the importance of liquidity in stock market performance. But, interest rates show a marginally significant negative impact, indicating the dampening effect of higher borrowing costs on equity investments. The real GDP demonstrates a strong positive correlation with the NEPSE index, underscoring the critical role of economic growth in boosting corporate earnings and investor confidence. Conversely, remittance inflows exhibit no significant relationship with stock market performance, perhaps reflecting their predominant use in consumption and real estate. The negative and highly substantial error correction term confirms that deviations from the long-run equilibrium are corrected rapidly in the subsequent period. These findings provide valuable insights for policymakers and stakeholders, emphasizing the role of macroeconomic stability in fostering sustainable growth in Nepal’s stock market.